The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1140/epjc/s10052-018-5699-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactive mixture of inhomogeneous dark fluids driven by dark energy: a dynamical system analysis

Abstract: We examine the evolution of an inhomogeneous mixture of non-relativistic pressureless cold dark matter (CDM), coupled to dark energy (DE) characterised by the equation of state parameter w < −1/3, with the interaction term proportional to the DE density. This coupled mixture is the source of a spherically symmetric Lemaître-Tolman-Bondi (LTB) metric admitting an asymptotic Friedman-Lemaître-Robertson-Walker (FLRW) background. Einstein's equations reduce to a 5-dimensional autonomous dynamical system involving … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 55 publications
(193 reference statements)
0
25
0
Order By: Relevance
“…Inhomogeneous dust with a positive cosmological constant given by the Lema ître-Tolman-Bondi (LTB) model was investigated in [74] and the critical points were examined in a unique way. Further recent studies in the inhomogeneous sector was conducetd with interactive mixture of dark fluids [75]. Interactive holographic dark energy models were explored in the light of stability analysis in Einstein's gravity [76] and other theories of gravity [77].…”
Section: Dynamical System and Stability Analysismentioning
confidence: 99%
“…Inhomogeneous dust with a positive cosmological constant given by the Lema ître-Tolman-Bondi (LTB) model was investigated in [74] and the critical points were examined in a unique way. Further recent studies in the inhomogeneous sector was conducetd with interactive mixture of dark fluids [75]. Interactive holographic dark energy models were explored in the light of stability analysis in Einstein's gravity [76] and other theories of gravity [77].…”
Section: Dynamical System and Stability Analysismentioning
confidence: 99%
“…We also mention that the evolution of an inhomogeneous mixture of nonrelativistic pressureless CDM, coupled to DE in which the interaction term proportional to the DE density was studied in Ref. [60]. Here, from the spherically symmetric Lemaître-Tolman-Bondi metric, the authors found that the interaction Q can be written as Q ∝ρ x as used in [23].…”
Section: Interacting Dynamics In Flat Flrwmentioning
confidence: 99%
“…For a comprehensive review on different interaction rates, we refer to [57,58]. We also note that the interaction between the dark sectors has also been examined in a more general framework where the geometry of the universe is inhomogeneous [59,60].…”
Section: Introductionmentioning
confidence: 99%
“…We have studied previously LTB metric models by means of the QL formalism [28,23,25,26,30,31,32], more recently considering as sources mixtures of nonrelativistic CDM, described as dust, coupled to DE described as a dark fluid with constant equation of state w < −1/3. In [30] we assumed the coupling term to be proportional to CDM energy density, while in [31] it was proportional to the DE density.…”
Section: Introductionmentioning
confidence: 99%
“…We have studied previously LTB metric models by means of the QL formalism [28,23,25,26,30,31,32], more recently considering as sources mixtures of nonrelativistic CDM, described as dust, coupled to DE described as a dark fluid with constant equation of state w < −1/3. In [30] we assumed the coupling term to be proportional to CDM energy density, while in [31] it was proportional to the DE density. In the present article we generalize these previous results by considering a coupling term proportional to the sum energy densities of both dark sources, considering as well a contribution of a baryonic matter source.…”
Section: Introductionmentioning
confidence: 99%